TEACHER PERSONAL BRANDING FROM THE PERSPECTIVE OF SYMBOLIC INTERACTIONISM - Mia Westina; Sudrajat (RADJA PUBLIKA, 2026)
The relational connection between students and teachers can determine the success of the learning process. This social relationship is driven by mutual sympathy between both parties. This mutual attraction is influenced by various factors, one of which is the teacher's self-image. The teacher's self-image is a subjective assessment by the students. Therefore, it is very important for teachers to build their personal branding to create a positive self-image. The label or image attached to teachers is a reflection of their professionalism. In the process of forming this self-image or image, teachers cannot be separated from the process of interpreting the symbols resulting from interactions and interpretations by students. This is then used by teachers to build their self-image. Building personal branding for teachers is part of the message of symbolic interactionism theory, where individuals give meaning to symbols in social interactions and influence teacher behavior. Social interaction is seen as a process within teachers to shape their self-image by considering the expectations of the students who are their interaction partners.